ANALISIS FAKTOR RIWAYAT BERAT BADAN LAHIR, PANJANG BADAB LAHIR, ASI EKSKLUSIF, DAN POLA NUTRISI PADA PADA KEJADIAN STUNTING - ULVA NOVIANA; mustofa haris; Diany yoke Savira (NHM PRESS, 2022)
Stunting is a chronic malnutrition problem that is caused by a lack of nutrition in a long time due to the provision of food that is not appropriate to nutritional needs. Based on a preliminary study survey at BPM Titik Sugiarti, S.ST Bangkalan for 5 months (April 2019 - September 2019) the number of LBW was 41 toddlers, the number of stunting babies was 35 toddlers (85.36%). The purpose of this study is to analyze the risk factors associated with stunting in infants (birth weight, birth length, exclusive breastfeeding, and nutritional patterns). The research design used was analytic with a retrospective approach. The independent variables examined were birth weight, birth length, exclusive breastfeeding, and nutritional patterns, and the dependent variable was stunting. The study population was 41 toddlers and the samples taken were 35 stunting toddlers at BPM Titik Sugiarti, S.ST Bangkalan. The sampling technique uses simple random sampling and data collection tools use observation sheets with chi square statistical tests. The results showed that there was a relationship between birth weight and the incidence of stunting with a value of ρ = 0.035 <(= 0.05, there was a relationship between the length of the birth body and the incidence of stunting with a value of ρ = 0.049 <(= 0.05, there was an exclusive association of breast milk with the occurrence of stunting with a value of ρ = 0.009 <(= 0.05, there is a relationship between the nutritional pattern and the occurrence of stunting with a value of ρ = 0.002 <(= 0.05. Based on the results of the study, midwives are expected to provide HE to mothers to mothers who will become pregnant so that their children will not experience stunting. Midwives are also expected to provide counseling about factors that are at risk of stunting so that the mother's nutrition is met and also provide prevention that can result in stunting so that their children will not experience stunting